2016
DOI: 10.1016/j.physb.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Role of substrate and annealing temperature on the structure of ZnO and AlxZn1−xO thin films for solar cell applications

Abstract: This paper reports on the deposition of pure and 5 at.% Al doped ZnO (AZO) prepared by sol-gel and applied to the substrates by spin-coating, and the role of annealing temperature on the crystallinity of these layers. It is found that both ZnO and AZO are largely amorphous when coated on glass compared to n-Si(111), as substrates. On both substrates, X-ray diffraction (XRD) shows that the crystallinity improves as annealing temperature is raised from 200 to 600 °C with better crystallinity on Si substrates. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
(48 reference statements)
2
7
0
1
Order By: Relevance
“…The elongation at break was 265% [68]. Nambala et al [69] studied the performances of ZnO and 5 at% Al-doped ZnO on glass and n-Si (111) backsheets by XRD, RBS, DRS and other techniques and found that the type of backsheets affected the crystallinity of the functional layers via interface effects, which thus affected the performance of the solar cells. The use of different materials and parameters for the protection and backsheet layers can also achieve mechanical improvement of solar cells.…”
Section: Mechanical Properties Of Protection and Backsheet Layersmentioning
confidence: 99%
“…The elongation at break was 265% [68]. Nambala et al [69] studied the performances of ZnO and 5 at% Al-doped ZnO on glass and n-Si (111) backsheets by XRD, RBS, DRS and other techniques and found that the type of backsheets affected the crystallinity of the functional layers via interface effects, which thus affected the performance of the solar cells. The use of different materials and parameters for the protection and backsheet layers can also achieve mechanical improvement of solar cells.…”
Section: Mechanical Properties Of Protection and Backsheet Layersmentioning
confidence: 99%
“… Schematic illustration of Au/ZnO NR/n-Si junction energy band diagram calculated using the SCAPS [ 34 ] simulation program. The electron affinities of Si (4.05 eV) and ZnO (4.35 eV), bandgaps of Si (1.12 eV) and ZnO (3.25 eV), and work function of Au (5.1 eV) were used in the calculations [ 35 ]. The trap states below the conduction band are illustrated in green.…”
Section: Figurementioning
confidence: 99%
“…A thermal conductivity value which is almost an order of magnitude lower than the bulk value for Al-doped ZnO has been reported [6], which illustrates the potential of thin films in improving the thermoelectric properties of ZnO. Doping the Zn sites with Al, Ga may enhance σ and change the conductive behavior from insulator through n-type semiconductor to metal by controlling the doping level [7][8][9]. Gadoped ZnO (GZO) film deposited on an Al 2 O 3 single crystal by pulsed laser deposition (PLD) technology shows an enhanced PF of about 57 μWm −1 K −2 at room temperature compared to the PF value of about 10 μWm −1 K −2 for pure ZnO film [9].…”
Section: Introductionmentioning
confidence: 98%